Connecting ‘Souths’. The Construction of Academic Networks between Latin America and Africa - Bayle, Paola Adriana (Íconos)
This article analyzes the strategies implemented by the Latin America Council of Social Sciences (CLACSO) designed to strengthen academic linkages between the peripheries of the World Academic System. The analysis focuses on the history behind the emergence of the Program for South-South Academic Cooperation in which CLACSO actively participates together with other institutions in the South. This policy –which began from the beginnigs of CLACSO (at the end of the 1960s and beginning of the 1970 s)– was oriented initially to establish linkages with academic institutions in Africa. It is believed that CLACSO developed this institutional policy in order to point out the assymetries in the World Academic System, constructed historically between academic centres and peripheries (North and South). In this system, global south academic actors are debilitated in their possibilities of production and circulation of knowledge. Initiatives of this type demonstrate that it is possible to limit the absolute domination of the academic centres over the peripheries.